2006
DOI: 10.1111/j.1528-1167.2006.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genetic Findings in 26 Italian Patients with Lafora Disease

Abstract: Summary:Purpose: EPM2B mutations have been found in a variable proportion of patients with Lafora disease (LD). Genotype-phenotype correlations suggested that EPM2B patients show a slower course of the disease, with delayed age at death, compared with EPM2A patients. We herein report clinical and genetic findings of 26 Italian LD patients.Methods: Disease progression was evaluated by means of a disability scale based on residual motor and cognitive functions and daily living and social abilities, at 4 years fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
77
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 10 publications
4
77
2
3
Order By: Relevance
“…Because exon 1 of the EPM2A gene encodes the carbohydrate-binding domain, a role for this domain in the childhood onset symptoms was suspected [Ganesh et al, 2002b]. Although no such report exists for the subdomains of NHLRC1 gene, independent reports have demonstrated that LD patients with NHLRC1 mutations tend to live longer than those with EPM2A mutations [Baykan et al, 2005;Franceschetti et al, 2006;GomezAbad et al, 2005;Singh et al, 2006]. Based on these findings, Singh et al (2006) proposed that not all functions of laforin could be regulated by malin.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because exon 1 of the EPM2A gene encodes the carbohydrate-binding domain, a role for this domain in the childhood onset symptoms was suspected [Ganesh et al, 2002b]. Although no such report exists for the subdomains of NHLRC1 gene, independent reports have demonstrated that LD patients with NHLRC1 mutations tend to live longer than those with EPM2A mutations [Baykan et al, 2005;Franceschetti et al, 2006;GomezAbad et al, 2005;Singh et al, 2006]. Based on these findings, Singh et al (2006) proposed that not all functions of laforin could be regulated by malin.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…The figure also shows (bottom) the genomic organization of the EPM2A gene and locations of the large deletions associated with LD. Mutations were tabulated from the following PubMed-indexed English articles reporting the mutations [Annesi et al, 2004;Franceschetti et al, 2006;Gomez-Garre et al, 2000Ganesh et al, 2002b;Ianzano et al, 2004;Ki et al, 2003;Lohi et al, 2007;Minassian et al, 1998Minassian et al, , 2000aMinassian et al, , 2000b …”
Section: Mutational Spectrum Of Epm2a and Nhlrc1 Genesmentioning
confidence: 99%
“…Bu durumdaki en büyük etkenin genetik heterojenite olduğu, genel olarak daha iyi seyirli LH tiplerinin NHLRC1'deki D146N mutasyonu ile ilişkili olabileceği ancak genotip-fenotip ilişkilendirmesi yapılmasının farklı kombinasyonlardaki 'farklı' mutasyonlar nedeniyle oldukça zor olduğu ifade edilmektedir. [7][8][9] Hastaların yaklaşık %80'inde genetik analizlerde gen mutasyonu saptanabilmektedir.…”
Section: Discussionunclassified
“…For examples, several of the NHLRC1 patients studied showed severe form LD 19 or a late onset LD, 20 and not all EPM2A patients with exon 1 mutations showed an early onset of the LD symptoms. 17,18 Intriguingly, a founder effect mutation for EPM2A in Arab families showed variable age at onset for LD, 21 suggesting that a specific …”
mentioning
confidence: 99%
“…6, 16 Here it was suggested that defects in the amino-terminal carbohydrate-binding domain of laforin, mainly coded by the first exon of the EPM2A gene, might underlie the early onset phenotype. 6 Although the proposed models were attractive, subsequent studies have shown that such genotype-phenotype correlations cannot be extended to several other group of patients, 17,18 suggesting that these models, at best, could be applicable to a few LD families. For examples, several of the NHLRC1 patients studied showed severe form LD 19 or a late onset LD, 20 and not all EPM2A patients with exon 1 mutations showed an early onset of the LD symptoms.…”
mentioning
confidence: 99%